The Importance of Cash and a SWOT analysis of the Limits on Cash Payments - Apanel Adrian Paweł (Studia Ekonomiczne i Regionalne)
The subject of the study was the characteristics of cash payments, their role in the payment system and the changing preferences of consumers toward cash and non-cash transactions. The purpose of the research was to gain knowledge about the importance of cash payments in everyday transactions, to assess their advantages and disadvantages compared to non-cash payments, and the effects of cash payment limits on the economy and society. The following research hypothesis was formulated: cash payments, despite the growing popularity of non-cash transactions, still play an important role in everyday transactions, and the introduction of cash payment limits, while it may contribute to increasing financial transparency and reducing the shadow economy, comes with challenges, such as digital exclusion and limiting consumers’ freedom of choice.